INTERNET ADDICTION AMONG YOUNG ADULT WORKERS: A REVIEW OF PSYCHOLOGY, SOCIOLOGY, AND ANTHROPOLOGY THROUGH A MIXED METHODS USING MACHINE LEARNING AI - Sasmita, Putu Bunga Amara; Murtidjaja, Erin Josephine (The Indonesian Journal of Social Studies, 2025)
The increasing internet usage in Indonesia has brought both positive impacts and new challenges, including internet addiction in the workplace. Internet addiction is characterized by uncontrolled, excessive online behavior, which can reduce productivity, mental health, and social functioning. This study examines internet addiction among formal workers through psychological, sociological, and anthropological perspectives. Psychologically, internet addiction is linked to low self-control, emotional distress, and sensation-seeking behavior. Sociologically, it reflects changing social norms and the human need to stay connected. Anthropologically, it highlights cultural shifts toward virtual interactions. A mixed-methods approach is used, combining qualitative exploration of subjective experiences with quantitative analysis to identify behavioral patterns using machine learning. This research aims to provide a comprehensive understanding of the individual, social, and cultural dimensions of internet addiction, emphasizing its significance in affecting daily life, mental health, and work performance.